2018
DOI: 10.1007/s11102-018-0895-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and treatment of central hypogonadism and hypoandrogenism in women with hypopituitarism

Abstract: In this first study of hypogonadism in women with hypopituitarism, using stringent diagnostic criteria for hypogonadism, the prevalence of central hypogonadism and low androgen levels was high and estrogen substitution was insufficient. Further studies are needed to elucidate the importance of hypogonadism and insufficient sex steroid replacement for the increased morbidity in hypopituitary women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Recently, it was documented in 184 consecutive women with GH replacement therapy that the oestrogen replacement treatment rate in women ≤ 52 years was lower compared to the replacement rates of the other pituitary hormone deficiencies (74% versus 100%); androgen replacement treatment was even lower in these women [71].…”
Section: Central Hypogonadism In Femalesmentioning
confidence: 99%
“…Recently, it was documented in 184 consecutive women with GH replacement therapy that the oestrogen replacement treatment rate in women ≤ 52 years was lower compared to the replacement rates of the other pituitary hormone deficiencies (74% versus 100%); androgen replacement treatment was even lower in these women [71].…”
Section: Central Hypogonadism In Femalesmentioning
confidence: 99%
“…Several studies have reported an increased risk of premature mortality in patients with hypopituitarism, and this risk is especially higher in women, mainly due to the higher risk of cardiovascular events (85,86). It has been suggested that the underdiagnosed and undertreated hormonal deficiencies could explain, at least in part, this increased mortality (87,88), and some studies have suggested that hypogonadism is a key factor behind this increased mortality in hypopituitary women (85,86).…”
Section: Functional Female Hypogonadismmentioning
confidence: 99%
“…Sex steroid replacement should be started in all women with HH who are at premenopausal age and be individualized for older women (30,68). Noteworthy, hypopituitarism removes the natural survival advantage that women have over men in terms of vascular complications; therefore, outcomes observed in natural menopause should not be extrapolated to women with frequently underdiagnosed and undertreated in women compared with men (77,78). While the goal of treatment of HH in older women is to control hot flushes, in young women, the goal is to prevent damage induced by estrogen deficiency.…”
Section: Sex Steroid Replacement Therapymentioning
confidence: 99%